2021
DOI: 10.1055/s-0041-1723989
|View full text |Cite
|
Sign up to set email alerts
|

U.S. COVID-19 State Government Public Dashboards: An Expert Review

Abstract: Background In the United States, all 50 state governments deployed publicly viewable dashboards regarding the novel coronavirus disease 2019 (COVID-19) to track and respond to the pandemic. States dashboards, however, reflect idiosyncratic design practices based on their content, function, and visual design and platform. There has been little guidance for what state dashboards should look like or contain, leading to significant variation. Objectives The primary objective of our study was to catalog h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…We conducted usability testing and think-aloud sessions with patients and providers. The aim of these interviews was to systematically collect feedback about the prototypes using a deductive approach based on our prior work on decision support tools [47,48]. We categorized identified themes into one of three categories: (1) function, issues that are related to meaningful and intuitive navigation of an application; (2) content, problems with information provided in an application that complicate or lead to misinterpretation of information; and (3) aesthetics, concerns that impede an application from having a minimalist design that effectively communicates information.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted usability testing and think-aloud sessions with patients and providers. The aim of these interviews was to systematically collect feedback about the prototypes using a deductive approach based on our prior work on decision support tools [47,48]. We categorized identified themes into one of three categories: (1) function, issues that are related to meaningful and intuitive navigation of an application; (2) content, problems with information provided in an application that complicate or lead to misinterpretation of information; and (3) aesthetics, concerns that impede an application from having a minimalist design that effectively communicates information.…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic brought to attention a longstanding need for welldesigned dashboards in public health and medicine [4]. It also brought to light that there are no uniform guiding principles behind developing publicly-facing dashboards intended to serve public interests.…”
Section: Guidance For the Design Of Public Dashboardsmentioning
confidence: 99%
“…It also brought to light that there are no uniform guiding principles behind developing publicly-facing dashboards intended to serve public interests. As a prime example, a recent review of United States (US) government public dashboards for COVID-19 found that "states engaged in dashboard practices that generally aligned with many of the goals set forth by the Centers for Disease Control and Prevention, Essential Public Health Services" (from abstract) [4]. However, the results of this review do not address whether the public was adequately served by any of these dashboards that were funded with the public's money.…”
Section: Guidance For the Design Of Public Dashboardsmentioning
confidence: 99%
“…In the United States, all 50 state governments use COVID-19 dashboards that are publicly available. These dashboards contain interactive maps and graphs and report indicators such as deaths, cases, and hospitalizations [31,32]. Widely used during the current pandemic, models have served a number of purposes, including predicting the spread of the virus [33][34][35][36][37] and for evaluating mitigation strategies [38][39][40].…”
Section: Principal Findingsmentioning
confidence: 99%